2021
DOI: 10.1080/02134748.2021.1942682
|View full text |Cite
|
Sign up to set email alerts
|

It is not enough to be a member: conditions for health benefits in associative participation (Ser miembro no es suficiente: condiciones en las que la participación asociativa reporta beneficios para la salud)

Abstract: Involvement in social and community activities has been identified as a key factor in health and well-being. This paper focuses on the health and well-being benefits of a particular type of group involvement: associative participation. The main aim is to identify the type of participation that brings more benefits to the members. Based on previous research, we expect that health and well-being would be higher when there is engagement with the association, when group involvement is more intense and when the typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…Moreover, Berkman and Syme (1979) showed that mortality is lower among those who participate in community life, and Cohen and Syme (1985) found a positive association between disease immunity and the number of social roles that a person plays. More recent research established a positive association between participation in associations and wellbeing (Fancourt and Steptoe, 2018), mental health (Seymour-Smith et al, 2017), and self-reported health (Gonzalez et al, 2020;Lima et al, 2021). Furthermore, shared group memberships impact health and wellbeing (Ysseldyk et al, 2018) by boosting individuals' selfesteem, belonging, meaning, sense of purpose, control, and efficacy in life (e.g., Cruwys et al, 2014;Greenaway et al, 2015;Jetten et al, 2017).…”
Section: Direct Links Between Close and Group Relationships And Healthmentioning
confidence: 99%
“…Moreover, Berkman and Syme (1979) showed that mortality is lower among those who participate in community life, and Cohen and Syme (1985) found a positive association between disease immunity and the number of social roles that a person plays. More recent research established a positive association between participation in associations and wellbeing (Fancourt and Steptoe, 2018), mental health (Seymour-Smith et al, 2017), and self-reported health (Gonzalez et al, 2020;Lima et al, 2021). Furthermore, shared group memberships impact health and wellbeing (Ysseldyk et al, 2018) by boosting individuals' selfesteem, belonging, meaning, sense of purpose, control, and efficacy in life (e.g., Cruwys et al, 2014;Greenaway et al, 2015;Jetten et al, 2017).…”
Section: Direct Links Between Close and Group Relationships And Healthmentioning
confidence: 99%
“…The different authors who have considered civic engagement in their studies have done so from different approaches, analyzing it in a more specific way and asking about certain behaviors (for example, asking whether they pay taxes and vote in elections) or in a more general way (for example, asking whether they are committed to serving in their community) (e.g., [5][6][7]). These civic behaviors have been positively related to mental and physical health and well-being in people who engage in them, and, in turn, the sense of community has been related to social well-being [8][9][10].…”
Section: Introductionmentioning
confidence: 99%